Prophylactic cranial irradiation for extensive stage small cell lung cancer: a meta-analysis of randomized controlled trials - Wang, Ziyi; Chen, Liang; Sun, Lu; Cai, Feng; Yang, Qiwei; Hu, Xiaohai; Fu, Qiang; Chen, Weiyang; Li, Peiwei; Li, Wenya (Frontiers in Oncology, 2023)
Background Previous studies have demonstrated that prophylactic cranial irradiation (PCI) could reduce the risk of brain metastases and prolong the overall survival (OS) of patients with small cell lung cancer (SCLC). However, it remains controversial whether the efficacy and safety of PCI would be subjected to the different characteristics of patients with extensive stage of SCLC. This meta-analysis aims to evaluate the efficacy and safety of PCI in patients with extensive stage SCLC. Methods PubMed, Embase, and the Cochrane Library were searched for relevant studies from inception to May, 2021. Hazard ratios (HRs) were used to measure the OS and progression-free survival (PFS), and relative risks (RRs) were employed to calculate the incidence of brain metastases, survival rate, and adverse events. Summary results were pooled using random-effect models. Results There were 1215 articles identified, and 15 trials were included, with a total of 1,623 participants. Patients who received PCI did not result in significantly improved OS [HR=0.87, 95%CI (0.70, 1.08) p=0.417] and PFS [HR=0.81, 95%CI (0.69, 0.95) p=0.001], compared with those who did not receive PCI, while patients who received PCI had a significantly decreased incidence of brain metastases [RR=0.57, 95%CI (0.45, 0.74), p<0.001]. PCI group showed no improvements in 2-year (RR=1.03, p=0.154), 3-year (RR=0.97, p=0.072), 4-year (RR=0.71, p=0.101) and 5-year survival rates (RR=0.32, p=0.307), compared with non-PCI group, whereas the overall RR indicated that PCI was associated with a higher 1-year survival rate [RR=1.46, 95%CI (1.08, 1.97), p=0.013]. In addition, PCI treatment was shown to be associated with increased incidence of adverse events, including fatigue, dermatitis, anorexia, nausea, vomiting, malaise, and cognitive impairment. Conclusion This meta-analysis suggests that PCI can reduce the incidence of brain metastases in extensive stage SCLC. Although PCI has no significant effect on the OS, it improves 1-year survival in patients with extensive stage SCLC. However, PCI may reduce 2,3,4,5-year survival and may result in a significantly increased risk of adverse events.